Review on techniques to improve the strength of adhesive joints with composite adherends. (15th November 2019) - Shang, X.; Marques, E.A.S.; Machado, J.J.M.; Carbas, R.J.C.; Jiang, D.; da Silva, L.F.M.
Abstract: The use of adhesive joints has increased rapidly in the past decades. Driven by the growing demand for lightweight structures, composite adherends have increased in popularity, benefiting from their high specific mechanical properties and design tailorability. However, composites are typically weak in the transverse direction, which can cause premature failure by delamination. Several techniques, aimed at reducing stress concentrations and increasing the transverse strength of the adherends, are discussed and compared in terms of material arrangement and geometry design. Lastly, a short summary on prominent features of the techniques is given. The paper is intended to provide guidelines for the design of adhesive joints with composite adherends.